Sociological thinking in contemporary organizational scholarship - Clegg, Stewart; Grothe-Hammer, Michael; Serrano-Velarde, Kathia (Research in the sociology of organizations, 2024)
The ebook edition of this title is Open Access and freely available to read online. Though organizational scholarship traces its intellectual lineage from a diversity of sources, there is little doubt that in recent years a key divide has emerged amongst organization scholars and sociologists. For many, if not most, it has become unclear what role sociology is supposed to play in organization studies. Against this backdrop, the editors of Sociological Thinking in Contemporary Organizational Scholarship ask: what is "organizational sociology" today? This pathbreaking volume explores the new boundaries of organizational sociology to identify, discuss and challenge sociology's genuine contribution to organization studies. Mapping a community of scholars that transcends disciplinary limitations, chapters follow one simple epistemic logic: society happens in, between, across and around organizations. Breathing fresh life into a once lively dialogue on the social nature, characteristics and consequences of the field, this is a valuable resource for navigating of the varied sociological scholarship we witness amongst today's organization scholars.